Joining forces to strengthen community seedbanks worldwide - Vernooy, Ronnie; Clancy, Evelyn; Diulgheroff, S.; Furman, B; González Santos, R.; Kajtna, B.; Marino, M.; Mushita, A.; Shrestha, P.; Song, Y.; Egon Sosinski, E.; Subedi, A.; et al. (Bioversity International, 2018)
Community seedbanks and emerging networks of community seedbanks contribute to the conservation and sustainable use of plant genetic resources for food and agriculture. Community seedbanks can secure improved access to and availability of diverse, locally adapted crops and varieties and enhance related indigenous knowledge and skills in plant management including seed selection, treatment, storage, multiplication and distribution. Two events were held in July 2018 in Rome, Italy to bring together representatives of organizations supporting community seedbanks from Africa, Asia, Europe and Latin America. This brief presents achievements, challenges, lessons learned and new opportunities in their countries and reflects on prospects of community seedbanks and their networks.